2021
DOI: 10.3390/plants10050950
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biochar on Indigenous Arbuscular Mycorrhizae Fungi from Agroenvironments

Abstract: The effects of biochar on soil–plant–microorganisms systems are currently being extensively investigated. Considering that arbuscular mycorrhizal fungi (AMF) play an essential role in nutrient dynamics, the present study aims at understanding vine shoot-derived biochar effects on AMF activity and the impact of their multiplication in soils on water-stress resistance of plants. Three agronomic tests were performed in greenhouse pots. The first experiment evaluated the effects of three factors: final pyrolysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…However, in order to determine the most appropriate biochar particle size it should also be considered aspects related to production, handling, and application systems, as well as ignition hazards and dust production issues. In this sense, the relatively large particle sizes tested in the present study was previously studied, and several benefits derived from its application were reported [46,61]. Considering the results obtained, the potential benefits of moistening biochar prior to the application depend on the final purpose and the type of biochar.…”
Section: Particle Size Distribution and Mechanical Processingmentioning
confidence: 61%
“…However, in order to determine the most appropriate biochar particle size it should also be considered aspects related to production, handling, and application systems, as well as ignition hazards and dust production issues. In this sense, the relatively large particle sizes tested in the present study was previously studied, and several benefits derived from its application were reported [46,61]. Considering the results obtained, the potential benefits of moistening biochar prior to the application depend on the final purpose and the type of biochar.…”
Section: Particle Size Distribution and Mechanical Processingmentioning
confidence: 61%
“…The environmental conditions of the rhizosphere soil changed the total abundance of AMF and flagellate spores. Depending on the soil conditions, this phenomenon may either positively or negatively impact the presence of indigenous AMF spores (Panahi et al 2020;Videgain-Marco et al 2021). The positive effect of biochar-amended soil on total AMF spores often occurs in soils experiencing abiotic stress (Jabborova et al 2021), while the negative impact on the form of a decrease in total AMF spores often occurs due to improvements in soil pH, P availability, and water availability (Liu et al 2019;.…”
Section: Discussionmentioning
confidence: 99%